2015
DOI: 10.7205/milmed-d-13-00353
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Suicidal Ideation and Suicide Attempts Among Deployed Danish Soldiers From 1990 to 2009

Abstract: On the basis of the results presented in this study, intervention against suicidal behavior would benefit from screening for certain childhood issues, drug abuse, and poor financial situation before deployment. During deployment, measures should be taken to minimize the amount of meaningless tasks and heavy workloads. At the same time, efficient ways of communicating with home should be ensured. After deployment, good athletic and recreation programs should be warranted for all military personnel-including rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Childhood physical abuse (Yehuda et al, 2015) is important to consider, for both suicide and violence in veterans (Begic & Jokic-Begic, 2001; Gallaway et al, 2012; Hellmuth et al, 2012; Lenhardt et al, 2012; MacManus et al, 2012; Stappenbeck et al, 2014; Youssef et al, 2013). Further, studies of veterans examining PTSD need also to analyze suicide and violence risk factors such as alcohol and drug abuse (Ejdesgaard, Zøllner, Jensen, Jørgensen, & Kähler, 2015; Elbogen et al, 2014b; Ganzini, Edwards, Surkan, & Drummond, 1995; Ilgen, Conner, Valenstein, Austin, & Blow, 2010; Jakupcak et al, 2007; Lehmann, McCormick, & Kizer, 1999; Owens et al, 2014), major depressive disorder (MDD) (Conner et al, 2014; Ilgen, Conner, et al, 2010; Nock et al, 2014; Pietrzak et al, 2011; Sherman, Sautter, Jackson, Lyons, & Han, 2006; Taft et al, 2005; Teten, Schumacher, Bailey, & Kent, 2009) or physical pain (Elbogen et al, 2014a; Ilgen, Zivin, et al, 2010; Kerns, Otis, Rosenberg, & Reid, 2003; Plagge, Lu, Lovejoy, Karl, & Dobscha, 2013).…”
mentioning
confidence: 99%
“…Childhood physical abuse (Yehuda et al, 2015) is important to consider, for both suicide and violence in veterans (Begic & Jokic-Begic, 2001; Gallaway et al, 2012; Hellmuth et al, 2012; Lenhardt et al, 2012; MacManus et al, 2012; Stappenbeck et al, 2014; Youssef et al, 2013). Further, studies of veterans examining PTSD need also to analyze suicide and violence risk factors such as alcohol and drug abuse (Ejdesgaard, Zøllner, Jensen, Jørgensen, & Kähler, 2015; Elbogen et al, 2014b; Ganzini, Edwards, Surkan, & Drummond, 1995; Ilgen, Conner, Valenstein, Austin, & Blow, 2010; Jakupcak et al, 2007; Lehmann, McCormick, & Kizer, 1999; Owens et al, 2014), major depressive disorder (MDD) (Conner et al, 2014; Ilgen, Conner, et al, 2010; Nock et al, 2014; Pietrzak et al, 2011; Sherman, Sautter, Jackson, Lyons, & Han, 2006; Taft et al, 2005; Teten, Schumacher, Bailey, & Kent, 2009) or physical pain (Elbogen et al, 2014a; Ilgen, Zivin, et al, 2010; Kerns, Otis, Rosenberg, & Reid, 2003; Plagge, Lu, Lovejoy, Karl, & Dobscha, 2013).…”
mentioning
confidence: 99%
“…The prevalences of suicide and SAs among Danish Army military personnel have in previous studies been found to be lower or at the same level as in the general Danish population. 47,48 Suicide rates among service members of the US Army have historically been lower than that of the general US population. However, that has changed in recent years, and the suicide rate of US service members is now higher than that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Research on protective factors indicates that many factors identified as protective for civilians, including family and social support, religious affiliation and participation, spirituality and meaning in life, a sense of control and effectiveness, and current mental health treatment, may also serve to protect military members from completing a suicide (Bryan, Graham, & Roberge, 2015;Pietrzak et al, 2010). Protective factors specific to the military documented by others include additional social support from the member's unit, perception of supportive leadership, strong peer-to-peer (i.e., soldier to soldier) relationships (Nock et al, 2013), and public support for military service (Ejdesgaard, Zollner, Jensen, Jorgensen, & Kahler, 2015). Indeed, the perception of social support specific to one's military unit has been shown to buffer against the negative effects of stress, the development of PTSD and other psychological disorders, and suicidality altogether (Skopp, Luxton, Bush, & Sirotin, 2011).…”
Section: Discussionmentioning
confidence: 99%